Biofabrication and Characterization Using Egg Shell Nanoparticles and their Haemolytic Analysis: An in-vitro Study - Dinesh, Y; Balu, Satheesh Kumar; Ramalingam, Karthikeyan; Ramani, Pratibha (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: Hydroxyapatite is a bioactive, biocompatible, and osteoconductive component having similar chemical characteristics to bone and tooth mineral components. Due to its porous structure and resistance to high temperatures, hydroxyapatite is commonly used as a catalyst and adsorbent. Eggshells are abundant in calcium carbonate, calcium phosphate, and other organic chemicals, making them excellent for CaO production. Materials and Methods: ES-Hap NPs from eggshell through an oil-bath-mediated precipitation technique. Egg shell nanoparticles were manufactured using chemical reagents like ammonia in a silicone oil bath. Preparation using a series of chemical reagents and characterization were done; functional groups were analysed using FTIR; and morphological analysis was analysed using FESEM. Hemolysis analysis was also done. Results: FTIR analysis showed functional PO4 groups, for the ES-Hap NPs at 1015 cm-1 and 563 cm-1, respectively. The XRD results based on crystallinity demonstrated Hap NPs of 20.86 nm. A FESEM investigation established the dimensions of NRs to be 78.15 nm and 221.62 nm, respectively. Crystallite size demonstrated that Hap NPs are comparable to normal human bone and may be employed as regenerative therapies. In addition, the hemolysis testing demonstrated superior blood compatibility compared to chemically manufactured, traditional Hap. Conclusion: These biogenic ES-Hap NPs can be further analysed for antimicrobial properties and in vivo studies, which could be highly beneficial for medical applications.
Keywords: Egg shell; Nanoparticles; Hemolytic analysis; XRD; FTIR; FESEM